Interference Effects of Spatial Color Design in Community Healthcare Environments during Epidemic - Yuan Feng, Muzi Qu (Forest Chemicals Review, 1970)
The outbreak of the new crown epidemic has brought enormous pressure on the healthcare system. Currently there is a long waiting time for big hospitals and an acute shortage of inpatient beds. Therefore, improving the community medical network so that people can enter the community for minor illnesses is one of the main means to solve the difficulties and high costs of s. At present, the environment of community medical places in China is not very satisfactory, the environments design mainly focuses on its functionality, Insufficient attention has been paid to optimizing the environmental design of community hospitals. This study summarizes the solution to improve the community medical environment simply and quickly through the transformation of environmental color by reading data, detailed analysis and field investigation.  By applying color space hierarchy design, humanized color design, functional division color design, and color-oriented design, we can provide a comfortable, beautiful, efficient, safe, and convenient color scheme for the hospital environment, which will have a positive intervention effect on patients’ physical, psychological, and physiological.